SANKSI PIDANA BAGI PELAKU TERORISME DALAM PERSPEKTIF HUKUM PIDANA ISLAM - Finka Safira, Mutiara; Barkah, Qodariah; Jumanah, Jumanah (Tazir, 2024)
Terrorism is an extraordinary crime and sanctions must also be extraordinary because acts of terrorism are politically motivated and the targets of terrorism can be civilian or non-civil, acts of terrorism are aimed at intimidating and influencing government policies, and acts of terrorism are carried out through acts that do not respect international law and ethics. However, in the decision Number: 5/Pid.Sus/2022/PT DKI, the defendant Taufiq Bulaga was only exiled for 19 years. Therefore, the researcher is interested in analyzing the Judge Decision Number: 5/Pid.Sus/2022/PT DKI in the Perspective of Islamic Criminal Law. This research is a library research, which is research conducted by examining library materials in the form of books, books, journals, and other sources. The technique in this study is a literature study, while the data collection is a secondary approach. The research approach used is an empirical normative approach, namely with a library research approach, which is a form of research whose data is obtained from the library. At this stage, the researcher seeks the theoretical basis of the research problem so that what is carried out is not a "trial and error" activity. Based on the results of the research, it was concluded that Decision Number: 5/Pid.Sus/2022/PT DKI according to the Islamic Criminal Law is a sentence of exile for the defendant Taufiq Bulaga, including in the act of hirabah where the defendant received a sentence of 19 years. In Islamic criminal law, participation in or direct commission of this criminal act of terrorism is not justified, because in essence it contains elements of dzoliman against fellow human beings. The defendant's motive for participating in the bombing was an element of revenge from the defendant because his family died during the bombing in Poso. While in Islam this is not justified. Because in Islam it is explained that between fellow humans must love each other and also stay in touch. So that there is a help in a good deed. Keywords: Sanctions, Terrorism, Islamic Criminal Law.